Surgical Treatment for Spasticity: Selective Dorsal Rhizotomy – Technique and Literature Review - Marcos Paulo dos Santos Teixeira (Thieme Revinter Publicações Ltda., 2018)
Spasticity is a motor disorder that leads to a resistance to passive joint movement. Cerebral palsy is the most important cause of spasticity and can be caused by several factors, including multiple gestations, alcoholism, infections, hemorrhages, drowning, and traumatic brain injuries, among others. There are many scales that help to measure and monitor the degree of impairment of these patients. The initial treatment should focus on the causal factor, such as tumors, inflammation, degenerative diseases, hydrocephalus, etc. Subsequently, the treatment of spastic musculature includes oral or intrathecal myorelaxants, spinal cord electrostimulation, neurotomies, Lissauer tract lesion, dentatotomy and selective dorsal rhizotomy. The latter is a safe technique, possible to be performed in most centers with neurosurgical support, and it is effective in the treatment of severe spasticity. In this article, the authors describe the surgical technique and conduct a review the literature.